Pengaruh Profesionalisme Guru PAK Terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 3 Sitio-Tio Kabupaten Samosir Tahun Pembelajaran 2022/2023 (Jurnal Pendidikan Agama dan Teologi, 2023)
The aim of this research is to determine the influence of PAK teacher professionalism on the learning interest of class VIII students at SMP Negeri 3 Sitio-tio Samosir Regency for the 2022/2023 academic year. The method used in this research is quantitative. The population is all students in class VIII of SMP Negeri 3 Sitio-tio Samosir Regency for the 2022/2023 academic year, totaling 50 people. Data was collected using a closed questionnaire of 40 items, namely 20 questionnaire items for variable Samosir 2022/2023 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.563 > rtable(=0.05,n=50) = 0.297, thus it is known that there is a positive relationship between variable X with variable Y. b) The significant relationship test obtained is the value tcount= 4.716 > ttable(=0.05,dk=n-2=48)= 2.021, thus there is a significant relationship between variable X and variable Y. 2) Test influence: a) Regression equation test, obtained regression equation Y ̂="34.775"+0.371X. b) Regression coefficient of determination test (r2) = 31.7%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=18, dk denominator=n-2=50-2=48) namely 22.24 > 1.51 Thus Ha accepted and H0 rejected.